1997
DOI: 10.7748/ns1997.04.11.29.34.c2449
|View full text |Cite
|
Sign up to set email alerts
|

How nurses perceive barriers to research implementation

Abstract: This article follows up a previous article on community nurses' perceived barriers to implementing research (Walsh 1997). Here the author examines the perceived barriers to research use among a sample of 63 hospital and 78 community nurses. The major barriers identified relate to the clinical setting and understanding research reports. The results have significant implications for managers of the service and educators who seek to promote research-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 0 publications
2
62
0
Order By: Relevance
“…These findings are consistent with previous studies, in which organizational support was cited as a top barrier (Bryar et al, 2003, Fink et al, 2005Funk et al, 1991b;Glacken & Chaney, 2004;Hutchinson & Johnston, 2004;LaPierre et al, 2004;McCleary & Brown, 2003;Parahoo & McCaughan, 2001;Retsas, 2000;Walczak et al, 1994;Walsh, 1997). A rank ordering of the 29 barriers and the percentage of items perceived by the registered nurses as great or moderate barriers are summarized in Table 2.…”
Section: Barriers To Research Utilizationsupporting
confidence: 91%
“…These findings are consistent with previous studies, in which organizational support was cited as a top barrier (Bryar et al, 2003, Fink et al, 2005Funk et al, 1991b;Glacken & Chaney, 2004;Hutchinson & Johnston, 2004;LaPierre et al, 2004;McCleary & Brown, 2003;Parahoo & McCaughan, 2001;Retsas, 2000;Walczak et al, 1994;Walsh, 1997). A rank ordering of the 29 barriers and the percentage of items perceived by the registered nurses as great or moderate barriers are summarized in Table 2.…”
Section: Barriers To Research Utilizationsupporting
confidence: 91%
“…This confers with previously documented studies of specialist and generalist nurses (Walsh 1997, Rutledge et al 1998, Dunn et al 1998, Kajermo et al 1998, Parahoo 2000, Retsas 2000, Bryar et al 2003.…”
Section: Discussionmentioning
confidence: 71%
“…In light of research utilisation studies of nurses from a range of clinical backgrounds (Funk et al 1991, Walsh 1997, Dunn et al 1998, Kajermo et al 1998, Rutledge et al 1998, Closs et al 2000, Parahoo 2000, Retsas 2000, Bryar et al 2003, the difficulty of obtaining, appraising and applying empirical research to directly meet the needs of patients is fraught with problems. Within the field of breast cancer, research activity has been particularly abundant and has resulted in an overwhelming quantity of published literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to promote a culture of research appreciation are hindered by two major barriers: the prevailing perception of research as a remote science and the absence of a supporting infrastructure (LeMay et al, 1998;Jowett et al, 2000;Parahoo, 2000). It has been suggested that a major cultural shift involving clinicians and researchers is essential to help practice become more research based and research to become more clinically relevant (Owen, 1995;Walsh, 1997;Whitford et al, 2000).…”
Section: Introductionmentioning
confidence: 99%